Prevalence and regional patterns of short birth intervals among women in Somalia - Salad Halane; Abdiwali Mohamed Ahmed; Mohamed Mustaf Ahmed; Jamilu Sani; Jamal Hassan Mohamoud; Abdihakim Elmi Abdishakur; Mustaf Mohamed Ibrahim; Najib Isse Dirie (Therapeutic Advances in Reproductive Health)
Background: Short birth intervals (SBI), defined as intervals of less than 33 months between consecutive live births, are a significant public health concern because of their association with adverse maternal and child health outcomes. Somalia has some of the highest maternal and neonatal mortality rates globally, compounded by limited access to family planning services. Objectives: This study aimed to provide a descriptive analysis of the prevalence and patterns of SBI among Somali women across regions, offering insight into maternal health policies. Design: A descriptive cross-sectional study design was employed. Methods: Data from 9288 women aged 15–49 years drawn from the Somali Demographic and Health Survey were analyzed. Descriptive statistics were used to examine the prevalence and distribution of SBI across regions and sociodemographic groups. Results: The overall prevalence of SBI was 77%, with regional disparities ranging from 82% in Togdheer and Hiraan to 74% in the Middle Shabelle. Women with no formal education and those in lower wealth quintiles exhibited a higher SBI prevalence than their counterparts. Rural and nomadic populations reported a higher SBI prevalence than urban residents, reflecting potential barriers to accessing family planning services. Conclusion: This study highlights the widespread prevalence of SBI in Somalia, with notable variations according to region, education, and economic status. These findings underscore the need for targeted interventions to address the geographic, educational, and economic barriers to family planning access.